The epidemiology of aggressive pituitary tumors (and its challenges) - Dekkers, Olaf M. (Rev Endocr Metab Disord, 2020)
Pituitary tumors are not rare if prevalence rates from autopsy or radiological series are considered; approximately 0.5% of all pituitary adenomas will come to medical attention. Less than 0.1% of these pituitary adenomas will become malignant, and probably around 0.5% of all detected adenomas will display an aggressive course. However, the exact incidence of both aggressive pituitary adenomas and pituitary carcinomas is unknown, as most data come from series with selected patients, such as surgically treated patients, which is likely not a reflection of all patients with a pituitary adenoma. An aggressive pituitary adenoma is not well-defined; even though an overarching definition, capturing both immunohistochemical and clinical characteristics is probably not waterproof, adoption of a widely accepted definition will be very helpful to harmonize research and establish more reliable epidemiological data.